Employment in refractory myasthenia gravis: A Myasthenia Gravis Foundation of America Registry analysis. Issue 6 (22nd October 2019) - Harris, Linda; Aban, Inmaculada B.; Xin, Haichang; Cutter, Gary
Abstract: Introduction: Labor‐market participation is potentially very difficult for patients with refractory myasthenia gravis (MG). In this study, employment status and work absences are compared between refractory and nonrefractory MG. Methods: Adults (aged 18–64 years, all diagnosed ≥2 years previously) were included if enrolled in the Myasthenia Gravis Foundation of America Patient Registry during July 2013 to February 2018. Results: Seventy‐six patients (9.2%) had refractory and 749 (90.8%) had nonrefractory disease; demographic data did not differ between groups. Relative to the nonrefractory group, the refractory group patients were more than twice as likely to work fewer hours per week (odds ratio [95% confidence interval]: currently employed, 2.777 [1.640–4.704]; employed over previous 6 months, 2.643 [1.595–4.380]), but those employed were not more likely to be absent from work. Discussion: Because absence from the labor market adversely affects quality of life and personal finances, these findings reaffirm the considerable disease burden associated with refractory MG.